Qualidade, compostos bioativos e atividade antioxidante de frutos de acessos de jerimum de leite (Cucurbita moschata) pertencentes ao Banco Ativo de Germoplasma de Cucurbitáceas da Embrapa Semiárido - Amariz, Andréia (2011)
The cucurbits are among the main crops present in the family agriculture in the Notheast, especially the pumpkin, indigenous species important for food both for culinary versatility and richness in minerals, vitamins and, in some species, carotenoids. The germplasm currently planted in most areas of the Northeast is devoid of features suitable for cultivation, as well as size, shape, firmness and flavor suitable to trade. Likewise, are not recognized materials with uniform attributes and nutritional properties, such as pro-vitamin A, which enable continuous improvement and secure the health and quality of life of low-income. The aim of this study was to evaluate the quality, the bioactive compounds and antioxidant activity of Cucurbita moschata accessions from the Cucurbits Active Germplasm Bank of Embrapa Tropical Semi-Arid that add quality to the market as well as characters useful for studies in plant breeding programs. Fifteen accessions were characterized: 510, 515, 525, 560, 561, 564, 574, 575, 579, 581, 583, 585, 587, 589 and 592, being from Piauí and Maranhão states. The evaluated characteristics were: weight, length, diameter, smaller, and the median longitudinal internal cavity, thickness of skin and pulp, firmness, lightness, chroma and angle of lesh color, soluble solids, total soluble sugars and starch, acidity, total extractable polyphenols, total carotenoids and β-carotene content, retinol activity equivalent, and the antioxidant activities by β-caroteno/Acid Linoleic and ABTS methods. Access 581 has added a greater number of postharvest desired characteristics and it is indicated for future work on plant breeding, aimed at obtaining higher quality fruit of Cucurbita moschata. Descriptors firmness and angle of flesh color, acidity, soluble sugars, β-carotene content and total antioxidant activity by the method β- caroteno/Acid Linoleic must be entered in future plant breeding work to assess the genetic diversity the species